Preparation method of nanoscale organic bentonite

By pulverizing, purifying, acidizing, sodiumizing, lithiating and chitosan modification of bentonite, combined with the use of composite organic modifiers, nano-scale organic bentonite was prepared, which solved the problems of poor dispersion and limited adsorption capacity of traditional bentonite, and significantly improved its application performance in organic systems.

CN119660756AInactive Publication Date: 2025-03-21HANGZHOU HEIDIS NEW MATERIAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411852697.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional bentonite has problems such as poor dispersion and limited adsorption capacity during application, which limits its application in organic systems.

Method used

Nano-scale bentonite is prepared by crushing, purifying and acidifying the bentonite raw ore powder, and then the composite bentonite is prepared by sodiumization, lithiation and chitosan modification treatment. Finally, organic modification is used for the composite organic modifier to form nano-scale organic bentonite.

Benefits of technology

It improves the dispersion, adsorption ability and compatibility of bentonite, enhances its application performance in organic systems, and improves its thermal stability and mildew resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190998760000131
    Figure BDA0005190998760000131
Patent Text Reader

Abstract

The invention relates to the technical field of organobentonite, in particular to a preparation method of nanoscale organobentonite, which is characterized in that fine crushing and purification treatment is performed on bentonite raw ore powder, and specific acidizing treatment steps are combined, so that not only can impurities be effectively removed, but also high-purity nanoscale preparation of bentonite can be realized; the activity and the reaction performance of the bentonite are improved, and a foundation is laid for subsequent sodium treatment and lithiation treatment; secondly, sodium bentonite and lithium bentonite are prepared through sodium treatment and lithiation treatment respectively, then the composite bentonite is prepared through mixing, the lithiation bentonite has excellent expansibility, thickening property and suspension property in water, low alcohol and low ketone, the sodium bentonite has good dispersity and cohesiveness, and the composite bentonite is prepared through mixing the sodium bentonite and the lithium bentonite. After the two are mixed and organically modified, the advantages of the two can be integrated, and the physical properties of the bentonite are further improved, for example, the expansion multiple is increased, the viscosity is increased, and the suspension stability is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic bentonite, and in particular to a method for preparing nano-scale organic bentonite. Background Art

[0002] Bentonite, as a layered silicate mineral, is widely used in various industrial fields, including drilling mud, ceramic manufacturing, papermaking, and environmentally friendly adsorbents, due to its unique physical and chemical properties, such as high specific surface area, good hygroscopicity and swelling. However, unmodified bentonite usually has high hydrophilicity and poor organic compatibility in its natural state, which limits its application in organic systems.

[0003] In recent years, with the continuous development of nanotechnology, bentonite has been successfully prepared into a new type of nanomaterial through the transformation and regulation of nanotechnology and has been widely used in various fields. However, traditional bentonite materials have problems such as poor dispersibility and limited adsorption capacity during application, which limits its application scope. In order to solve these problems, researchers began to explore methods for organic modification of bentonite to improve its dispersibility, adsorption capacity and compatibility. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing nano-scale organic bentonite, which can effectively solve the problems of poor dispersibility, adsorption capacity and compatibility of bentonite in the prior art.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing nano-scale organic bentonite, the preparation method comprising:

[0007] S1. After crushing and purifying the bentonite ore powder, the powder is subjected to acidification treatment to obtain nano-grade bentonite;

[0008] S2, sodiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain sodium-based bentonite, lithiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain lithium-based bentonite, and chitosan-modifying 1 / 3 of the total weight of the nano-grade bentonite to obtain chitosan-modified bentonite;

[0009] S3. The sodium-based bentonite, lithium-based bentonite and chitosan-modified bentonite are mixed to obtain composite bentonite, which is then organically modified using a composite organic modifier to obtain nano-scale organic bentonite.

[0010] Furthermore, the specific method of the crushing and purification process in S1 is:

[0011] The bentonite ore powder was crushed and passed through a 200-mesh sieve, immersed in pure water at a solid-liquid ratio of 1:20, stirred at a speed of 500 r / min for 1 hour, and allowed to stand for 1 hour to separate the upper suspension. The upper suspension was then centrifuged at a speed of 6000 r / min for 5 minutes. After removing the supernatant, the precipitate was placed in an oven at 85°C and dried for 6 hours. After ball milling and passing through a 200-mesh sieve, the crushing and purification process was completed.

[0012] Furthermore, the specific steps of the acidification treatment in S1 are:

[0013] Step A, preparing an acidulant by mixing a 30% sulfuric acid solution, a 35% hydrochloric acid solution and a 30% acetic acid solution in a volume ratio of 5:5:2, and then mixing the bentonite ore powder after crushing and purification with the acidulant in a solid-liquid ratio of 1:3, and the obtained mixture is recorded as an acidulant component;

[0014] Step B, placing the acidified component at a constant temperature of 85°C and stirring at a speed of 600r / min for 50min, then oscillating and activating in a constant temperature water bath at 70°C for 3h, rinsing with deionized water three times and centrifuging at a speed of 6000r / min for 15min, the resulting precipitate is placed in an oven at 85°C and dried for 6h, then ball-milled and sieved through a 200-mesh sieve to obtain nano-bentonite.

[0015] Furthermore, the preparation method of sodium bentonite in S2 is:

[0016] Nano-bentonite was mixed with deionized water at a solid-liquid ratio of 1:10 to prepare a slurry, and then sodium carbonate with a mass of 3% of the nano-bentonite was added to the slurry. The mixture was stirred at 150 r / min for 1 hour at a temperature of 80°C and then centrifuged at 8000 r / min for 1 minute. The resulting precipitate was placed in an oven at 105°C and dried for 2 hours. The precipitate was ground through a 200-mesh sieve to obtain sodium bentonite.

[0017] Furthermore, the preparation steps of lithium bentonite in S2 are:

[0018] Step i, weighing 0.8 g of lithium carbonate, adding it into 10 g of 10% oxalic acid solution, stirring at a speed of 100 r / min for 10 min, and recording it as the lithium solution component;

[0019] Step ii, nano-bentonite is mixed with deionized water at a solid-liquid ratio of 1:20 to prepare a slurry, and then a lithium liquid component with a weight of 40% of the nano-bentonite is added, and after stirring at a temperature of 80°C and a speed of 150r / min for 1.5h, a sodium hydroxide solution with a mass fraction of 15% is added dropwise to adjust the pH value to 8, and then centrifuged at a speed of 6000r / min for 5min to obtain a precipitate and rinsed with deionized water 3 times, placed in an oven at 95°C for 4h, and then ground through a 200-mesh sieve to obtain lithium-based bentonite.

[0020] Furthermore, the preparation method of chitosan-modified bentonite in S2 is:

[0021] Weigh 3g of chitosan and pour it into 100mL of 5% glacial acetic acid solution. Stir at a stirring speed of 300r / min for 30min, then add 60g of nano-bentonite, stir at a stirring speed of 200r / min for 4h in a water bath temperature of 45℃, then centrifuge at a speed of 4000r / min for 5min. The obtained precipitate is washed three times with deionized water by centrifugation and placed in an oven at 80℃ for 4h. After grinding through a 100-mesh sieve, the obtained product is chitosan-modified bentonite.

[0022] Furthermore, the specific operation of the mixing treatment in S3 is: pouring sodium bentonite, lithium bentonite and chitosan-modified bentonite into a ball mill and ball milling for 30 minutes, and then stirring at a stirring speed of 300 r / min for 10 minutes, and the result is composite bentonite.

[0023] Furthermore, the preparation method of the composite organic modifier in S3 is:

[0024] Hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and stearic acid are weighed and mixed in a weight ratio of 3:2:1 to obtain a composite organic modifier.

[0025] Furthermore, the specific steps of the organic modification treatment in S3 are:

[0026] Step 1, weighing 8-12 parts by weight of composite bentonite, dispersing it in 200 parts by weight of deionized water, stirring and dispersing it to obtain a bentonite suspension, weighing 1-2 parts by weight of composite organic modifier, dispersing it in 40 parts by weight of deionized water, stirring and dissolving it to obtain a modifier aqueous solution;

[0027] Step 2: drop the aqueous solution of the modifier into the bentonite suspension, stir and react at 80°C for 3h, remove the filtrate by suction, rinse with deionized water for 3-5 times, dry in an oven at 80°C for 24h, and grind through a 200-mesh sieve to obtain nano-organic bentonite.

[0028] Furthermore, the specific operation of stirring and dispersing in step 1 is stirring at a speed of 500r / min for 10min, the specific operation of stirring and dissolving in step 1 is stirring at a speed of 600r / min for 10min, the dripping rate in step 2 is 1 drop / s, and the speed of stirring reaction in step 2 is 200r / min.

[0029] Beneficial effects of the present invention:

[0030] 1. The present invention can effectively remove impurities and realize high-purity nano-scale preparation of bentonite by finely crushing and purifying bentonite ore powder, combined with a specific acidification treatment step, thereby improving the activity and reaction performance of bentonite and laying a good foundation for subsequent sodium treatment and lithium treatment; secondly, the present invention obtains sodium-based bentonite and lithium-based bentonite through sodium treatment and lithium treatment respectively, and then obtains composite bentonite by mixing. The lithium-based bentonite has excellent swelling, thickening and suspension properties in water, lower alcohols and lower ketones, and the sodium-based bentonite has good dispersibility and adhesion. After mixing the two and performing organic modification, the advantages of the two can be combined to further improve the physical properties of the bentonite, such as increasing the swelling multiple, increasing the viscosity, and enhancing the suspension stability; in addition, the bentonite is modified with chitosan, which can give the bentonite good biocompatibility and adsorption properties. Combined with the antibacterial properties of chitosan itself, the bentonite modified by chitosan can have good mildew resistance.

[0031] 2. The present invention first mixes hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and stearic acid, and then uses the mixed composite organic modifier to organically modify bentonite, which can reduce the surface tension between bentonite particles on the basis of giving bentonite a wider adsorption range, making it easier to disperse in water to form a stable suspension, and the surface properties of bentonite can be changed through the modification of the composite organic modifier, so that its compatibility with organic solvents or organic systems is improved, which is conducive to the application in organic systems; secondly, the organic modifier molecules can be inserted into the interlayer of bentonite to increase its interlayer distance, thereby increasing the adsorption capacity and diffusion rate of bentonite, and the organically modified bentonite has higher thermal stability and can maintain the stability of its structure and performance at higher temperatures. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing nano-scale organic bentonite in this embodiment is as follows:

[0035] S1. After crushing and purifying the bentonite ore powder, the powder is subjected to acidification treatment to obtain nano-grade bentonite;

[0036] Among them, the specific method of crushing and purification is:

[0037] The bentonite ore powder was crushed and passed through a 200-mesh sieve, immersed in pure water at a material-liquid ratio of 1:20, stirred at a speed of 500 r / min for 1 hour, and allowed to settle for 1 hour to separate the upper suspension. The upper suspension was then centrifuged at a speed of 6000 r / min for 5 minutes, and the supernatant was removed and the precipitate was placed in an oven at 85°C and dried for 6 hours. The crushing and purification process was completed after ball milling and passing through a 200-mesh sieve.

[0038] The specific steps of acidification treatment are:

[0039] Step A, preparing an acidulant by mixing a 30% sulfuric acid solution, a 35% hydrochloric acid solution and a 30% acetic acid solution in a volume ratio of 5:5:2, and then mixing the bentonite ore powder after crushing and purification with the acidulant in a solid-liquid ratio of 1:3, and the obtained mixture is recorded as an acidulant component;

[0040] Step B, placing the acidified component at a constant temperature of 85°C and stirring at a speed of 600r / min for 50min, then oscillating and activating in a constant temperature water bath at 70°C for 3h, rinsing with deionized water three times and centrifuging at a speed of 6000r / min for 15min, the resulting precipitate is placed in an oven at 85°C and dried for 6h, then ball-milled and sieved through a 200-mesh sieve to obtain nano-bentonite.

[0041] S2, sodiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain sodium-based bentonite, lithiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain lithium-based bentonite, and chitosan-modifying 1 / 3 of the total weight of the nano-grade bentonite to obtain chitosan-modified bentonite;

[0042] Wherein, the preparation method of sodium bentonite is:

[0043] The nano-bentonite is mixed with deionized water at a solid-liquid ratio of 1:10 to prepare a slurry, and then sodium carbonate is added to the slurry in an amount of 3% by mass of the nano-bentonite, and the mixture is stirred at a speed of 150 r / min for 1 hour at a temperature of 80° C., and then centrifuged at a speed of 8000 r / min for 1 minute, and the obtained precipitate is placed in an oven at 105° C. and dried for 2 hours, and the obtained precipitate is ground through a 200-mesh sieve to obtain sodium-based bentonite;

[0044] The preparation steps of lithium bentonite are:

[0045] Step i, weighing 0.8 g of lithium carbonate, adding it into 10 g of 10% oxalic acid solution, stirring at a speed of 100 r / min for 10 min, and recording it as the lithium solution component;

[0046] Step ii, mixing nano-bentonite with deionized water at a solid-liquid ratio of 1:20 to prepare a slurry, then adding a lithium liquid component with a weight of 40% of the nano-bentonite, stirring at a temperature of 80°C and a speed of 150r / min for 1.5h, adding a sodium hydroxide solution with a mass fraction of 15% to adjust the pH value to 8, then centrifuging at a speed of 6000r / min for 5min to obtain a precipitate and washing it with deionized water 3 times, placing it in an oven at 95°C and drying it for 4h, and then grinding it through a 200-mesh sieve to obtain lithium-based bentonite;

[0047] The preparation method of chitosan modified bentonite is:

[0048] Weigh 3g of chitosan and pour it into 100mL of 5% glacial acetic acid solution. Stir at a stirring speed of 300r / min for 30min, then add 60g of nano-bentonite, stir at a stirring speed of 200r / min for 4h in a water bath temperature of 45℃, then centrifuge at a speed of 4000r / min for 5min. The obtained precipitate is washed three times with deionized water by centrifugation and placed in an oven at 80℃ for 4h. After grinding through a 100-mesh sieve, the obtained product is chitosan-modified bentonite.

[0049] S3, preparing composite bentonite by mixing sodium bentonite, lithium bentonite and chitosan-modified bentonite, and performing organic modification with a composite organic modifier to obtain nano-scale organic bentonite;

[0050] The specific operation of the mixing treatment is as follows: pouring sodium bentonite, lithium bentonite and chitosan-modified bentonite into a ball mill and ball milling for 30 minutes, and then stirring at a stirring speed of 300 r / min for 10 minutes, and the obtained result is composite bentonite;

[0051] The preparation method of the composite organic modifier is:

[0052] Hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and stearic acid are weighed and mixed in a weight ratio of 3:2:1 to obtain a composite organic modifier.

[0053] The specific steps of organic modification treatment are:

[0054] Step 1, weighing 8 parts by weight of composite bentonite and dispersing it in 200 parts by weight of deionized water, stirring at a speed of 500 r / min for 10 minutes to obtain a bentonite suspension, weighing 1 part by weight of a composite organic modifier and dispersing it in 40 parts by weight of deionized water, stirring at a speed of 600 r / min for 10 minutes to obtain a modifier aqueous solution;

[0055] Step 2: drip the modifier aqueous solution into the bentonite suspension at a dripping rate of 1 drop / s, stir and react at a temperature of 80°C and a speed of 200 r / min for 3 hours, remove the filtrate by suction, rinse with deionized water 3 times, place in an oven at 80°C and dry for 24 hours, then grind through a 200-mesh sieve to obtain nano-grade organic bentonite.

[0056] Example 2

[0057] A method for preparing nano-scale organic bentonite in this embodiment is as follows:

[0058] S1. After crushing and purifying the bentonite ore powder, the powder is subjected to acidification treatment to obtain nano-grade bentonite;

[0059] Among them, the specific method of crushing and purification is:

[0060] The bentonite ore powder was crushed and passed through a 200-mesh sieve, immersed in pure water at a material-liquid ratio of 1:20, stirred at a speed of 500 r / min for 1 hour, and allowed to settle for 1 hour to separate the upper suspension. The upper suspension was then centrifuged at a speed of 6000 r / min for 5 minutes, and the supernatant was removed and the precipitate was placed in an oven at 85°C and dried for 6 hours. The crushing and purification process was completed after ball milling and passing through a 200-mesh sieve.

[0061] The specific steps of acidification treatment are:

[0062] Step A, preparing an acidulant by mixing a 30% sulfuric acid solution, a 35% hydrochloric acid solution and a 30% acetic acid solution in a volume ratio of 5:5:2, and then mixing the bentonite ore powder after crushing and purification with the acidulant in a solid-liquid ratio of 1:3, and the obtained mixture is recorded as an acidulant component;

[0063] Step B, placing the acidified component at a constant temperature of 85°C and stirring at a speed of 600r / min for 50min, then oscillating and activating in a constant temperature water bath at 70°C for 3h, rinsing with deionized water three times and centrifuging at a speed of 6000r / min for 15min, the resulting precipitate is placed in an oven at 85°C and dried for 6h, then ball-milled and sieved through a 200-mesh sieve to obtain nano-bentonite.

[0064] S2, sodiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain sodium-based bentonite, lithiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain lithium-based bentonite, and chitosan-modifying 1 / 3 of the total weight of the nano-grade bentonite to obtain chitosan-modified bentonite;

[0065] Wherein, the preparation method of sodium bentonite is:

[0066] The nano-bentonite is mixed with deionized water at a solid-liquid ratio of 1:10 to prepare a slurry, and then sodium carbonate is added to the slurry in an amount of 3% by mass of the nano-bentonite, and the mixture is stirred at a speed of 150 r / min for 1 hour at a temperature of 80° C., and then centrifuged at a speed of 8000 r / min for 1 minute, and the obtained precipitate is placed in an oven at 105° C. and dried for 2 hours, and the obtained precipitate is ground through a 200-mesh sieve to obtain sodium-based bentonite;

[0067] The preparation steps of lithium bentonite are:

[0068] Step i, weighing 0.8 g of lithium carbonate, adding it into 10 g of 10% oxalic acid solution, stirring at a speed of 100 r / min for 10 min, and recording it as the lithium solution component;

[0069] Step ii, mixing nano-bentonite with deionized water at a solid-liquid ratio of 1:20 to prepare a slurry, then adding a lithium liquid component with a weight of 40% of the nano-bentonite, stirring at a temperature of 80°C and a speed of 150r / min for 1.5h, adding a sodium hydroxide solution with a mass fraction of 15% to adjust the pH value to 8, then centrifuging at a speed of 6000r / min for 5min to obtain a precipitate and washing it with deionized water 3 times, placing it in an oven at 95°C and drying it for 4h, and then grinding it through a 200-mesh sieve to obtain lithium-based bentonite;

[0070] The preparation method of chitosan modified bentonite is:

[0071] Weigh 3g of chitosan and pour it into 100mL of 5% glacial acetic acid solution. Stir at a stirring speed of 300r / min for 30min, then add 60g of nano-bentonite, stir at a stirring speed of 200r / min for 4h in a water bath temperature of 45℃, then centrifuge at a speed of 4000r / min for 5min. The obtained precipitate is washed three times with deionized water by centrifugation and placed in an oven at 80℃ for 4h. After grinding through a 100-mesh sieve, the obtained product is chitosan-modified bentonite.

[0072] S3, preparing composite bentonite by mixing sodium bentonite, lithium bentonite and chitosan-modified bentonite, and performing organic modification with a composite organic modifier to obtain nano-scale organic bentonite;

[0073] The specific operation of the mixing treatment is as follows: pouring sodium bentonite, lithium bentonite and chitosan-modified bentonite into a ball mill and ball milling for 30 minutes, and then stirring at a stirring speed of 300 r / min for 10 minutes, and the obtained result is composite bentonite;

[0074] The preparation method of the composite organic modifier is:

[0075] Hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and stearic acid are weighed and mixed in a weight ratio of 3:2:1 to obtain a composite organic modifier.

[0076] The specific steps of organic modification treatment are:

[0077] Step 1, weighing 12 parts by weight of composite bentonite and dispersing it in 200 parts by weight of deionized water, stirring at a speed of 500 r / min for 10 minutes to obtain a bentonite suspension, weighing 2 parts by weight of a composite organic modifier and dispersing it in 40 parts by weight of deionized water, stirring at a speed of 600 r / min for 10 minutes to obtain a modifier aqueous solution;

[0078] Step 2: drip the modifier aqueous solution into the bentonite suspension at a dripping rate of 1 drop / s, stir and react at a temperature of 80°C and a speed of 200 r / min for 3 hours, remove the filtrate by suction, rinse with deionized water 5 times, place in an oven at 80°C and dry for 24 hours, then grind through a 200-mesh sieve to obtain nano-grade organic bentonite.

[0079] Example 3

[0080] A method for preparing nano-scale organic bentonite in this embodiment is as follows:

[0081] S1. After crushing and purifying the bentonite ore powder, the powder is subjected to acidification treatment to obtain nano-grade bentonite;

[0082] Among them, the specific method of crushing and purification is:

[0083] The bentonite ore powder was crushed and passed through a 200-mesh sieve, immersed in pure water at a material-liquid ratio of 1:20, stirred at a speed of 500 r / min for 1 hour, and allowed to settle for 1 hour to separate the upper suspension. The upper suspension was then centrifuged at a speed of 6000 r / min for 5 minutes, and the supernatant was removed and the precipitate was placed in an oven at 85°C and dried for 6 hours. The crushing and purification process was completed after ball milling and passing through a 200-mesh sieve.

[0084] The specific steps of acidification treatment are:

[0085] Step A, preparing an acidulant by mixing a 30% sulfuric acid solution, a 35% hydrochloric acid solution and a 30% acetic acid solution in a volume ratio of 5:5:2, and then mixing the bentonite ore powder after crushing and purification with the acidulant in a solid-liquid ratio of 1:3, and the obtained mixture is recorded as an acidulant component;

[0086] Step B, placing the acidified component at a constant temperature of 85°C and stirring at a speed of 600r / min for 50min, then oscillating and activating in a constant temperature water bath at 70°C for 3h, rinsing with deionized water three times and centrifuging at a speed of 6000r / min for 15min, the resulting precipitate is placed in an oven at 85°C and dried for 6h, then ball-milled and sieved through a 200-mesh sieve to obtain nano-bentonite.

[0087] S2, sodiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain sodium-based bentonite, lithiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain lithium-based bentonite, and chitosan-modifying 1 / 3 of the total weight of the nano-grade bentonite to obtain chitosan-modified bentonite;

[0088] Wherein, the preparation method of sodium bentonite is:

[0089] The nano-bentonite is mixed with deionized water at a solid-liquid ratio of 1:10 to prepare a slurry, and then sodium carbonate is added to the slurry in an amount of 3% by mass of the nano-bentonite, and the mixture is stirred at a speed of 150 r / min for 1 hour at a temperature of 80° C., and then centrifuged at a speed of 8000 r / min for 1 minute, and the obtained precipitate is placed in an oven at 105° C. and dried for 2 hours, and the obtained precipitate is ground through a 200-mesh sieve to obtain sodium-based bentonite;

[0090] The preparation steps of lithium bentonite are:

[0091] Step i, weighing 0.8 g of lithium carbonate, adding it into 10 g of 10% oxalic acid solution, stirring at a speed of 100 r / min for 10 min, and recording it as the lithium solution component;

[0092] Step ii, mixing nano-bentonite with deionized water at a solid-liquid ratio of 1:20 to prepare a slurry, then adding a lithium liquid component with a weight of 40% of the nano-bentonite, stirring at a temperature of 80°C and a speed of 150r / min for 1.5h, adding a sodium hydroxide solution with a mass fraction of 15% to adjust the pH value to 8, then centrifuging at a speed of 6000r / min for 5min to obtain a precipitate and washing it with deionized water 3 times, placing it in an oven at 95°C and drying it for 4h, and then grinding it through a 200-mesh sieve to obtain lithium-based bentonite;

[0093] The preparation method of chitosan modified bentonite is:

[0094] Weigh 3g of chitosan and pour it into 100mL of 5% glacial acetic acid solution. Stir at a stirring speed of 300r / min for 30min, then add 60g of nano-bentonite, stir at a stirring speed of 200r / min for 4h in a water bath temperature of 45℃, then centrifuge at a speed of 4000r / min for 5min. The obtained precipitate is washed three times with deionized water by centrifugation and placed in an oven at 80℃ for 4h. After grinding through a 100-mesh sieve, the obtained product is chitosan-modified bentonite.

[0095] S3, preparing composite bentonite by mixing sodium bentonite, lithium bentonite and chitosan-modified bentonite, and performing organic modification with a composite organic modifier to obtain nano-scale organic bentonite;

[0096] The specific operation of the mixing treatment is as follows: pouring sodium bentonite, lithium bentonite and chitosan-modified bentonite into a ball mill and ball milling for 30 minutes, and then stirring at a stirring speed of 300 r / min for 10 minutes, and the obtained result is composite bentonite;

[0097] The preparation method of the composite organic modifier is:

[0098] Hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and stearic acid are weighed and mixed in a weight ratio of 3:2:1 to obtain a composite organic modifier.

[0099] The specific steps of organic modification treatment are:

[0100] Step 1, weighing 10 parts by weight of composite bentonite and dispersing it in 200 parts by weight of deionized water, stirring it at a speed of 500 r / min for 10 minutes to obtain a bentonite suspension, weighing 2 parts by weight of a composite organic modifier and dispersing it in 40 parts by weight of deionized water, stirring it at a speed of 600 r / min for 10 minutes to obtain a modifier aqueous solution;

[0101] Step 2: drip the modifier aqueous solution into the bentonite suspension at a dripping rate of 1 drop / s, stir and react at a temperature of 80°C and a speed of 200 r / min for 3 hours, remove the filtrate by suction, rinse with deionized water 4 times, place in an oven at 80°C and dry for 24 hours, then grind through a 200-mesh sieve to obtain nano-grade organic bentonite.

[0102] Comparative Example 1

[0103] The preparation method of a nano-scale organic bentonite provided in this comparative example is substantially the same as that in Example 1, the main difference being that in this comparative example 1, the composite bentonite in Example 1 is replaced by the sodium-based bentonite in Example 1.

[0104] Comparative Example 2

[0105] The preparation method of a nano-scale organic bentonite provided in this comparative example is substantially the same as that in Example 1, the main difference being that in this comparative example 2, the composite bentonite in Example 1 is replaced by the lithium-based bentonite in Example 1.

[0106] Comparative Example 3

[0107] The preparation method of a nano-scale organic bentonite provided in this comparative example is substantially the same as that in Example 1, the main difference being that in this comparative example 3, the composite bentonite in Example 1 is replaced with chitosan-modified bentonite.

[0108] Comparative Example 4

[0109] The preparation method of a nano-scale organic bentonite provided in this comparative example is substantially the same as that in Example 1, the main difference is that in this comparative example 4, the composite organic modifier in Example 1 is replaced with a single hexadecyltrimethylammonium bromide.

[0110] Comparative Example 5

[0111] The preparation method of a nano-scale organic bentonite provided in this comparative example is substantially the same as that in Example 1, the main difference being that in this comparative example 5, the composite organic modifier in Example 1 is replaced with a single hexadecyl dimethyl benzyl ammonium chloride.

[0112] Comparative Example 6

[0113] The preparation method of a nano-scale organic bentonite provided in this comparative example is substantially the same as that in Example 1, the main difference being that in this comparative example 6, the composite organic modifier in Example 1 is replaced with a single stearic acid.

[0114] Performance Testing

[0115] The nano-scale organic bentonites prepared in Examples 1-3 and Comparative Examples 1-6 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-6 was tested with reference to the standard of GB / T27798-2011, and the obtained data are recorded in the following table:

[0116]

[0117] It can be seen from the data in the above table that the nano-scale organic bentonite prepared in Examples 1-3 has higher colloid value, swelling capacity and swelling value than that in Comparative Examples 1-6, indicating that the nano-scale organic bentonite prepared in the present invention has better dispersibility and swelling properties, and has better market application value.

[0118] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing nano-scale organic bentonite, characterized in that: The preparation method is: S1. After crushing and purifying the bentonite ore powder, the powder is subjected to acidification treatment to obtain nano-grade bentonite; S2, sodiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain sodium-based bentonite, lithiumizing 1 / 3 of the total weight of the nano-grade bentonite to obtain lithium-based bentonite, and chitosan-modifying 1 / 3 of the total weight of the nano-grade bentonite to obtain chitosan-modified bentonite; S3. The sodium-based bentonite, lithium-based bentonite and chitosan-modified bentonite are mixed to obtain composite bentonite, which is then organically modified using a composite organic modifier to obtain nano-scale organic bentonite.

2. The method for preparing a nano-scale organic bentonite according to claim 1, characterized in that: The specific method of crushing and purifying in S1 is: The bentonite ore powder was crushed and passed through a 200-mesh sieve, immersed in pure water at a solid-liquid ratio of 1:20, stirred at a speed of 500 r / min for 1 hour, and allowed to stand for 1 hour to separate the upper suspension. The upper suspension was then centrifuged at a speed of 6000 r / min for 5 minutes. After removing the supernatant, the precipitate was placed in an oven at 85°C and dried for 6 hours. After ball milling and passing through a 200-mesh sieve, the crushing and purification process was completed.

3. The method for preparing a nano-scale organic bentonite according to claim 1, characterized in that: The specific steps of acidification treatment in S1 are: Step A, preparing an acidulant by mixing a 30% sulfuric acid solution, a 35% hydrochloric acid solution and a 30% acetic acid solution in a volume ratio of 5:5:2, and then mixing the bentonite ore powder after crushing and purification with the acidulant in a solid-liquid ratio of 1:3, and the obtained mixture is recorded as an acidulant component; Step B, placing the acidified component at a constant temperature of 85°C and stirring at a speed of 600r / min for 50min, then oscillating and activating in a constant temperature water bath at 70°C for 3h, rinsing with deionized water three times and centrifuging at a speed of 6000r / min for 15min, the resulting precipitate is placed in an oven at 85°C and dried for 6h, then ball-milled and sieved through a 200-mesh sieve to obtain nano-bentonite.

4. The method for preparing a nano-scale organic bentonite according to claim 1, characterized in that: The preparation method of sodium bentonite in S2 is: Nano-bentonite was mixed with deionized water at a solid-liquid ratio of 1:10 to prepare a slurry, and then sodium carbonate with a mass of 3% of the nano-bentonite was added to the slurry. The mixture was stirred at 150 r / min for 1 hour at a temperature of 80°C and then centrifuged at 8000 r / min for 1 minute. The resulting precipitate was placed in an oven at 105°C and dried for 2 hours. The precipitate was ground through a 200-mesh sieve to obtain sodium bentonite.

5. The method for preparing a nano-scale organic bentonite according to claim 1, characterized in that: The preparation steps of lithium bentonite in S2 are: Step i, weighing 0.8 g of lithium carbonate, adding it into 10 g of 10% oxalic acid solution, stirring at a speed of 100 r / min for 10 min, and recording it as the lithium solution component; Step ii, nano-bentonite is mixed with deionized water at a solid-liquid ratio of 1:20 to prepare a slurry, and then a lithium liquid component with a weight of 40% of the nano-bentonite is added, and after stirring at a temperature of 80°C and a speed of 150r / min for 1.5h, a sodium hydroxide solution with a mass fraction of 15% is added dropwise to adjust the pH value to 8, and then centrifuged at a speed of 6000r / min for 5min to obtain a precipitate and rinsed with deionized water 3 times, placed in an oven at 95°C for 4h, and then ground through a 200-mesh sieve to obtain lithium-based bentonite.

6. The method for preparing nano-organic bentonite according to claim 1, characterized in that: The preparation method of chitosan modified bentonite in S2 is: Weigh 3g of chitosan and pour it into 100mL of 5% glacial acetic acid solution. Stir at a stirring speed of 300r / min for 30min, then add 60g of nano-bentonite, stir at a stirring speed of 200r / min for 4h in a water bath temperature of 45℃, then centrifuge at a speed of 4000r / min for 5min. The obtained precipitate is washed three times with deionized water by centrifugation and placed in an oven at 80℃ for 4h. After grinding through a 100-mesh sieve, the obtained product is chitosan-modified bentonite.

7. The method for preparing nano-organic bentonite according to claim 1, characterized in that: The specific operation of the mixing treatment in S3 is: pouring sodium bentonite, lithium bentonite and chitosan-modified bentonite into a ball mill and ball milling for 30 minutes, and then stirring at a stirring speed of 300 r / min for 10 minutes, and the result is composite bentonite.

8. The method for preparing nano-organic bentonite according to claim 1, characterized in that: The preparation method of the composite organic modifier in S3 is: Hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and stearic acid are weighed and mixed in a weight ratio of 3:2:1 to obtain a composite organic modifier.

9. The method for preparing nano-organic bentonite according to claim 1, characterized in that: The specific steps of the organic modification treatment in S3 are: Step 1, weighing 8-12 parts by weight of composite bentonite, dispersing it in 200 parts by weight of deionized water, stirring and dispersing it to obtain a bentonite suspension, weighing 1-2 parts by weight of composite organic modifier, dispersing it in 40 parts by weight of deionized water, stirring and dissolving it to obtain a modifier aqueous solution; Step 2: drop the aqueous solution of the modifier into the bentonite suspension, stir and react at 80°C for 3h, remove the filtrate by suction, rinse with deionized water for 3-5 times, dry in an oven at 80°C for 24h, and grind through a 200-mesh sieve to obtain nano-organic bentonite.

10. The method for preparing nano-scale organic bentonite according to claim 9, characterized in that: The specific operation of stirring and dispersing in step 1 is stirring at a speed of 500 r / min for 10 min, the specific operation of stirring and dissolving in step 1 is stirring at a speed of 600 r / min for 10 min, the dripping rate in step 2 is 1 drop / s, and the speed of stirring reaction in step 2 is 200 r / min.

Citation Information

Patent Citations

  • Production method of environment-friendly chitosan intercalation composite bentonite adsorbent

    CN101757886A

  • Semidry method for preparation of organic intercalated type montmorillonite

    CN104211076A

  • Preparation method of nanoscale organobentonite

    CN104760968A

  • Easy-to-disperse sodium bentonite and preparation method thereof

    CN105293511A

  • High-purity high-thickening easily-dispersed nano montmorillonite applied to field of water-based coatings and preparation method thereof

    CN111269606A